Caring for torture survivors: one of the most difficult but fulfilling jobs in medicine. (6th February 2020) - Silberner, Joanne
Abstract : Angela Burnett has been working with torture survivors in London for two and a half decades, listening to their stories and chronicling the lasting physical and mental health effects. Joanne Silberner asked her about how and why she does it